2021
DOI: 10.1126/sciadv.abf9394
|View full text |Cite
|
Sign up to set email alerts
|

A live single-cell reporter assay links intratumor heterogeneity to metastatic proclivity in Ewing sarcoma

Abstract: Targeting of the most aggressive tumor cell subpopulations is key for effective management of most solid malignancies. However, the metastable nature of tumor heterogeneity, which allows cells to transition between strong and weak tumorigenic phenotypes, and the lack of reliable markers of tumor-promoting properties hamper identification of the most relevant cells. To overcome these obstacles, we designed a functional microRNA (miR)–based live-cell reporter assay to identify highly tumorigenic cells in xenotra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The inactivation of EPHB2 accelerates the occurrence of CRC. Besides, EPHB2 mutations are closely associated with tumor suppression in gastric cancer and involved in the prognosis and metastasis of other tumors such as Ewing sarcoma ( Davalos et al, 2007 ; Keskin et al, 2021 ). ATOH1 is a target of the JNK1 and MUC2 pathways and closely associated with the proliferation, invasion, and metastasis of CRC cells ( Shen et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…The inactivation of EPHB2 accelerates the occurrence of CRC. Besides, EPHB2 mutations are closely associated with tumor suppression in gastric cancer and involved in the prognosis and metastasis of other tumors such as Ewing sarcoma ( Davalos et al, 2007 ; Keskin et al, 2021 ). ATOH1 is a target of the JNK1 and MUC2 pathways and closely associated with the proliferation, invasion, and metastasis of CRC cells ( Shen et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of EphB2 increases the aggressiveness of EwS2 in threedimensional cultures. The miR-145 enabled us to identify EphB2 as a facilitator of EwS metastasis, which can serve both as a predictor of tumor behavior and as a potential therapeutic target for eliminating that most adventitious cell [47].…”
Section: Eph/ephrin and Ewing's Sarcomamentioning
confidence: 99%
“…The EWSR1::FLI1/ERG fusion oncoproteins function as activators and repressors of gene expression (7). Several recent studies have suggested that genes typically repressed by EWSR1::FLI1/ERG fusion proteins may become activated due to variable fusion protein levels or external stimuli and that such changes in gene expression may contribute to the development of metastatic EWS (8)(9)(10)(11). Repressed EWSR1::FLI1/ERG gene targets include many encoding proteins involved in cell-cell and cell-extracellular interactions, specifically proteins involved in actin cytoskeletal organization, extracellular matrix (ECM)-receptor interactions, and focal adhesion formation -processes associated with cell migration and invasion (9).…”
Section: Introductionmentioning
confidence: 99%